SOLO ISLAMIC PLAYGROUP - Mayasari, laila (2016)
Solo Islamic Playgroup is a body of early childhood education and also / age ( 5-0 years in particular ) with preschools designed will take place on the road solo-purwodadi surakarta .Methods used in educating , nursing and develop learning activity , give religious norms and play for the students .In the design process and design this place employed the concept of modern architecture .The son of this child education should be given the opportunity to get to know the creation of the lord . In addition to getting education well , children are need to play while berekreasi that can be mengembangakan their talent and her creativity .In surakarta place to submit children , educating children , channel their talent and her creativity , and recreation are separated so that it difficult to mobility parents .Because terpisahnya the place , so peep out the idea to design a forum in order to accommodate all activities in one container namely solo islamic preschools .Solo islamic preschools are the crucible education are located in the solo as a learning and children played an early age under 5 years having the characteristics of basic Islamic.